Conflitos de identidade entre os jovens da etnia Tikuna na comunidade de Umariaçu I na terra indígena Eware I no município de Tabatinga/AM - Sousa, Sebastião Rocha de (2013)
This paper deals with the issue of the identity of the Tikuna youth, of the Umariaçu I Community on the Eware I Indigenous Territory in the municipality of Tabatinga, AM, based on contemporary challenges. The Tikuna are a people who inhabit the Amazon region, who have preserved part of their cultural tradition in spite of the contact with the non-indigenous. The role of education in the maintenance and reinterpretation of the Tikuna heritage is analyzed as well as their ritual reinvention. The Tikuna youth have before them the attempt of insertion in the modern world with the preservation of the traditions received from their ancestors. This position generates conflicts with the older ones and deepens the identity crises inherent to adolescence. The Young Girl Festivity rite carries out an attempt of connecting the past and the future, since it reinterprets the ritual obligations in a new context. In this resides the wealth of the Tikuna culture for the interpretation of inter-culturality in a pluriethnic society.